Organization of city police on the Charter of the Deanery (1782). - I. Konovalov; B. Shimanis (Правоприменение)
УДК 340The subject. The subject of analysis in the article is the organization of the city police of the Russian Empire under the Charter of the Deanery 1782. Special attention is given to the structure and legal issues of the activities of local government and its interaction with the local administrative authorities.The purpose. The growing interest in the history of local government connects not only with the aspiration of historians to look more deeply into the past but also with practical needs. Researching of the forgotten traditions of public administration allows to take greater account of historical experience that has been accumulated over the centuries as well as use it in legislation and law enforcement. We also need to take a look at already known facts and events in the light of today's realities.Methodology. Theoretical and methodological basis of the research are such principles of historical knowledge as objectivity, historicism, determinism, alternativeness and social ap-proach which are assuming an unbiased approach to the analysis of the researched problems, as well as a critical attitude to sources.Results, scope of application. The article describes the process of codification in the administrative legislation of the Russian Empire and also organization of local governance in the Russian Empire according with Charter of the Deanery. The basic aspects police activities are also characterized. This approach may overcome the old myths and misconceptions in the sphere of police organization and also prevent the birth of new ones.Conclusions. This act created the system of local police management which was centralized by establishing of the police bodies with number of state employees, specified in the law. Such institutes became both representatives of the sovereign power in the provinces and guides of its policies until reforms of the 60s and 70s of the 19 century.